The effects of daytime napping on psychophysiological measures in physically active individuals and athletes: A systematic review, meta-analysis, and meta-regression, with assessment of the certainty of evidence - Boukhris, O.; Trabelsi, K.; Suppiah, H.; Jahrami, H.; Driller, M. (Biology of Sport, 2026)
To synthesise the impacts of napping following normal sleep (NS) or deprived sleep on psychophysiological measures in physically active individuals and athletes. This systematic review and meta analysis utilized nine databases, including Web of Science, PubMed/MEDLINE, Scopus, SPORTDiscus, Embase, ProQuest Central, Cochrane Library, PsycInfo, and SciElo, to evaluate the effects of napping in physically active individuals and athletes, focusing on psychophysiological measures. The risk of bias in the included studies was assessed using the Cochrane Collaboration`s RoB 2.0 tool, while the certainty of evidence (CoE) was evaluated using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluations) approach. In the 35 studies, 489 participants (athletes or physically active) were studied. Following NS, napping significantly reduced total mood score (standardized mean difference (SMD)=0.61), fatigue (SMD=0.91), rating of perceived exertion (RPE) both during (SMD=1.62) and immediately after exercise (SMD=1.11). Additionally, napping significantly improved perceived recovery (SMD=1.66). There were no significant effects of napping on sleepiness (SMD=1.09), muscle soreness (SMD=1.57), heart rate during exercise (SMD=0.62), and temperature (SMD=0.66). Similarly, following sleep deprivation, there were no significant effects of napping on sleepiness (SMD=1.03) and fatigue (SMD=0.79). The CoE was rated as moderate for RPE during and after exercise following NS, while it was low to very low for the remaining outcomes. Napping has been found to positively impact only fatigue, mood states, perceived exertion, and recovery following NS in physically active individuals and athletes. The low-to-very low CoE requires cautious interpretation, highlighting the need for further napping studies implementing robust methodologies.